ISOLATION IDENTIFICATION AND PATHOTYPING OF NEWCASTLE DISEASE VIRUSES FORM NATURALLY INFECTED CHICKENS IN IRAQI KURDISTAN REGION - & Odisho, Ahmed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Iraq has been endemic for Newcastle disease virus (NDV) with natural infection causing significant losses in the poultry industry since 1968. This study was designed to  identify a natural infection of NDV  occurred in three governorate in the northern part of Iraq (Erbil, Sulymaniyah and Duhok)  among chicken flocks and estimate its virulence  by the mean death times(MDT) and intra-cerebral pathogenicity index (ICPI). Ninety six flocks with high mortality were examined for post mortem lesions and the samples collected from suspected ND chicken flocks, either sick or dead showed characteristic clinical findings and show positive rapid test for NDV antigen. The collected samples were  pooled, homogenized and centrifuged then the virus propagted in embryonated chicken eggs was confirmed by real time RT-PCR, hemagglutination (HA) test and  hemagglutination inhibition (HI) test using anti-NDV hyper-immune serum. The results were isolation 9(12%) out of 96 samples where NDV was positive clinicaly. The MDT and ICPI revealed that the isolates were compatible to mesogenic (1/9) and velogenic (5/9) types. These results demonstrated that the NDV strains were virulent for chickens and the vaccination might not give enough protection.